(untitled) (Experimental biology, 2021)
Adaptive cell immunotherapy namely combination of dendritic cells (DC) and cytokine-induced killer (CIK) cells is a promising tool in treating various types of cancer and choosing the appropriate technique of tumour antigens obtaining is a challenging issue. CIK cells also called NKT cells are an in vitro propagated population of cells characterized by hybrid NK cells and T cells phenotype. DCs are highly specialized antigen-presenting cells, which uptake, process and present antigens to effector cells of the immune system. In this study, we compared the effect of tumour antigens obtained by different methods on dendritic cells maturation and their ability to activate CIK cells. Cytotoxicity of CIK cells, generated in two different conditions (whole blood or peripheral blood mononuclear cells), was accessed using SW620 cells as a target by MTT assay. According to obtained results, CIK cells expanded from whole blood showed significantly strong anti-tumoral activity compared to CIK cells generated from peripheral blood mononuclear cells isolated by Histopaque-1077 density gradient centrifugation. Also, we determined that all examined methods of antigen preparation can be used, but only in the case of antigen-loaded DCs cocultivation with CIK cells. Key words: Сytokine-induced killer cell, dendritic cell, immunogenic cell death, damage-associated molecular pattern, TNF-alpha.